Monetary Dynamics and Inflation in an Emerging Economy: Evidence from a Vecm Approach Incorporating Consumer Expectations - Tony S. Chendrawan; Umayatu Suiroh Suharto; Lilis Hoeriyah (Riviera Publishing, 2026)
This research examines the dynamics of inflation in the macroeconomic framework by emphasizing the role of monetary factors and expectations in the formation of inflation. This research uses the VECM econometric approach with data from the time series for the period 2014Q1–2025Q4. The analysis stages include stationariness test (ADF), optimal lag determination, VAR stability test, Johansen cointegration test, VECM estimation, as well as Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) analysis. Empirical results show that in the short-term inflation was influenced by inertia factors and consumer expectations, while in the long term the money supply and consumer expectations are the main determinants of inflation. In addition, there is a relatively rapid adjustment mechanism towards long-term equilibrium, as well as the increasing contribution of external variables in explaining inflation variations as the time horizon increases. This study concludes that inflation is not only a monetary phenomenon, but also greatly influenced by people's expectations. Implicitly, monetary policy needs to focus not only on controlling liquidity, but also on managing expectations through credibility and policy communication. These findings confirm the importance of a comprehensive approach in maintaining price stability.